Ethanol CO2 Reforming over Cu/Al2O3 Catalyst for Syngas Production - Nor Shafiqah, Mohd Nasir; Mahadi, Bahari; Lau, N. Jun; Fayaz, Fahim; Vo, Dai-Viet N. (Universiti Malaysia Pahang, 2018)
ethanol CO2 reforming (ECR) over 10%Cu/Al2O3 catalyst was investigated for production of syngas. The catalyst was synthesized by implemented incipient wetness impregnation method and characterized by using X-ray diffraction (XRD). ECR was evaluated in a stainless steel fixed-bed reactor by varying reaction temperature from 973 K to 1023 K. XRD analysis indicated the formation of CuO phases and eventually reduce to Cu metallic during H2 reduction. The ethanol and carbon dioxide conversion reached until 55.39% and 38.91% respectively at 1023 K reaction temperature. Furthermore, H2/CO ratio was obtained below 2 which is ideal for Fisher-Tropsch synthesis (FTS).